Unexpected Interruptions, Idle Time, and Creativity: Evidence from a Natural Experiment - Schweisfurth, Tim G.; Greul, Anne (Organization Science, 2024)
Interruptions are common in organizational life and last from seconds and minutes to hours and days. We rely on a quantitative abductive strategy to determine how extended work interruptions shape employees’ creativity. We start by studying how surprising interruptions that cause idle time affect employees’ creative performance. We do so by exploiting a natural experiment—a supply chain shortage that caused unexpected stops in production plants—to show that individuals exposed to such an interruption produce 58% more ideas than uninterrupted employees in the three weeks after the interruption. We corroborate this effect in a replication and extend it to idea quality. Investigating the effect’s causes, we then show that we do not find the same effects for two other interruption types: for unexpected interruptions without idle time (i.e., intrusions), we find a negative effect on creative performance because employees forcefully disengage from their work and switch their attention to the interrupting task. For expected interruptions with idle time (i.e., planned breaks), we also find no positive effect on creative performance because employees discretionally disengage from work and focus on nonwork and leisure goals. We consider and evaluate three different theoretical explanations for our findings: attention residue, cognitive stimulation, and recovery. We end our abductive process by putting attention residue forward as the most likely explanation. Finally, we suggest three propositions based on our findings and discuss our contributions to the literature on interruptions and creativity in organizations. Funding: T. G. Schweisfurth acknowledges funding from the Tempowerk Technology Center Hamburg.